Cooperative Learning Model with ICT Media Towards Children's Mathematical Literacy - Ramadan, Awalia Nor; Meilanie, R Sri Martini; Rahayu, Wardani (Jurnal Ilmiah POTENSIA, 2025)
The learning problems in early childhood in Indonesia that are currently faced are increasingly complex, not only from the pedagogical side of teachers but also faced with low mathematical literacy learning outcomes. Therefore, in early childhood learning, it is necessary to design a cooperative model with ICT media that can answer the challenges of the needs of the times. The purpose study is to measure the influence of cooperative learning with the help of ICT media on the improvement of mathematical literacy skills in children. This study is a quasi-experimental research with treatment by level 2x2 factorial Nonequivalence Posttest-Only Control Design, using mixed methods such as interviews and observations. Based on intensive processes and observations, the findings of this study show that the cooperative model with ICT media affects children's mathematical literacy skills. This is proven by the results of the ANAVA test obtained Fcount = 7.437 < Ftable = 161 and a significance value of 0.008 < 0.05, then it is concluded that there is a difference in the results and the results of the t-test show the acquisition of a score tcount = 23.662 with df = 87, so that ttable = 1.98761, tcount  ttable With the results of 23,662 > 1.9796, the literacy ability of children who were given the cooperative model treatment was higher than that of the group who were taught with the conventional learning model.